Situational analysis study of the agriculture sector in Uganda - Magunda, Matthias (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Uganda submitted its first Nationally Determined Contribution (NDC) in 2015 to the UNFCCC through which it committed to reduce approximately 22% of national GHG emissions in 2030 compared to business-as-usual of 49 million MtCO2eq. The country is currently in the process of updating its NDC in accordance with decision 1/CP.21 of the UNFCCC. As part of the process, the Ministry of Agriculture, Animal Industry and Fisheries (MAAIF) is leading the process of defining the sector’s medium- and long-term low emissions, climate development pathway (Agricultural LTS) in order to identify concrete short-, medium- and long term adaptation and mitigation options that would inform updating of the agricultural component of the Nationally Determined Contributions (NDCs) and successive NDCs. As a precursor to the LTS, understanding the status of the sector (baseline) is critical. This situational analysis study assessed the current status and trends of the agriculture sector in Uganda and identified opportunities to transform the sector towards a low carbon and climate resilient development pathway.